G248 Long term survival of children from a cluster randomised controlled trial of women's participatory groups in makwanpur district, nepal. (27th April 2015) - Heys, M; Manandhar, DS; Osrin, D; Tumbahangphe, KM; Sen, A; Shrestha, B; Shrestha, DK; Adhikari, RK; Budhathoki, B; Costello, A
Abstract : Background: Women's groups practicing a participatory action learning approach (WPGs) to addressing issues around pregnancy, childbirth and newborn and child health have been shown in a number of trials in low income countries and on their meta-analysis to significantly reduce maternal and neonatal mortality. 1 Their long term impact on survival has never been explored. Aims: To assess the long term impact of exposure to WPGs on maternal and child mortality in participants of the first cRCT of WPGs in Makwanpur District, rural Nepal (2001–2003). 2 Methods: Outcome data were collected by interview from the mother or the household head or from wider family members or neighbours where the family had moved. Analysis was carried out on an intention to treat basis using the a priori analysis plan in the original trial. 2 Sensitivity analyses were performed using individual and cluster level comparison of person-years. Results: A total of 5824 mothers and 6078 children were alive 4 weeks postpartum (Figure 1 ). Reliable outcome data were available for 74.2% (4321) and 72.5% (4406) and probable outcomes for a further 24.8% (1452) and 26.8% (1630) of mothers and children respectively. On individual analysis, children born into the intervention clusters had 32% reduced risk of mortality after 4 weeks of age up to age of follow-up compared to those born into the control clusters (Table 1 ; Odds ratio (OR): 0.68, confidence interval (CI): 0.51, 0.92). Multilevel modelling adjusting for the effects of clustering and pairing of clusters showed a similar effect size, (OR: 0.69 CI: 0.49, 0.96; Table 1 ). Analyses using child mortality rates per person years are more conservative and the effect size smaller and non-statistically significant (however, this method does not take into account pairing of clusters, nor variation in size of clusters, Table 3 ) Fewer women in the intervention clusters died than control clusters, but the difference was not statistically significant. (Figure 1, Table 2 ). Conclusion: Our findings suggest there are long term survival benefits for children of WPGs beyond the neonatal period. Long term follow-up of other trials of WPGs are warranted. References: Prost A, Colbourn T, Seward N, et al . Women's groups practising participatory learning and action to improve maternal and newborn health in low-resource settings: a systematic review and meta-analysis. Lancet 2013;381 :1736–46 Manandhar DS, Osrin D, Shrestha BP, et al . Effect of a participatory intervention with women's groups on birth outcomes in Nepal: cluster-randomised controlled trial. Lancet 2004;364 :970–9